“Community participation and sustainability of national water projects: The case study of Chalinze water supply project in Bagamoyo district - Shayo, Deogratias (Mzumbe University, 2024)
A dissertation submitted to the School of Public Administration in partial fulfilment of the requirements for the award of Master of Public Administration (MPA) Degree of Mzumbe University